2016
DOI: 10.1016/s2215-0366(16)00083-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an integrated telehealth service for patients with depression: a pragmatic randomised controlled trial of a complex intervention

Abstract: National Institute for Health Research (NIHR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 27 publications
2
83
0
Order By: Relevance
“…In fact, overall, eHealth is becoming an everyday term and is, to various degrees, permeating the lives of many. For instance, in a recent study, Salisbury et al (2016) conducted a trial test of the effectiveness of integrating a (multicomponent) telehealth intervention into general practice for the treatment and management of depression. The need of telemedicine is, however, not confined to mental disease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, overall, eHealth is becoming an everyday term and is, to various degrees, permeating the lives of many. For instance, in a recent study, Salisbury et al (2016) conducted a trial test of the effectiveness of integrating a (multicomponent) telehealth intervention into general practice for the treatment and management of depression. The need of telemedicine is, however, not confined to mental disease.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the effectiveness of the intervention is likely to require better targeting of the intervention to those interested in using it, efforts to improve patient engagement and more effective optimisation of anti-depressant medication when patients fail to respond to treatment. 14 In conclusion, the Healthlines service was found to be acceptable to patients as a means of condition management, 18 and response to treatment after 4 months was higher for participants randomised to the intervention. 14 However, the intervention was associated with a small incremental QALY gain at 12 months and was not likely to be cost-effective at a threshold value of £20 000.…”
Section: Limitationsmentioning
confidence: 83%
“…14 Analysis of secondary trial outcomes indicated greater improvements in anxiety, and greater satisfaction with support, among those randomised to the intervention. 14 The second consideration is that analysis of correlation (using Spearman's rho) indicates that high PHQ-9 scores (indicating greater severity of depression) and low EQ-5D scores (indicating lower quality of life) are correlated at baseline and all followup time points. The null of independence was rejected in each case (P<0.001), and the absolute value of the correlations were largest with the anxiety/depression domain of the EQ-5D instrument.…”
Section: Discussionmentioning
confidence: 99%
“…When implemented effectively, these technologies can be used to increase access to timely, quality, or specialty care [2][3][4][5][6][7] ; monitor disease progression 2,6 ; improve adherence to treatment regimens 8,9 ; and even improve patient outcomes. 2,6,[10][11][12][13] Despite gains in routine health care, adoption of PT as a mainstream tool remains limited in interventional clinical research and the pharmaceutical industry. 14 In 2016, a survey of pharmaceutical trial sponsors, eConsent vendors, and contract research organizations (CROs) reported only 28 pharmaceutical trials in 12 countries that had successfully used eConsent to consent patients.…”
Section: Introductionmentioning
confidence: 99%